Pattern‐triggered immunity restricts host colonization by endophytic fusaria, but does not affect endophyte‐mediated resistance. (18th November 2020) - de Lamo, Francisco J.; Šimkovicová, Margarita; Fresno, David H.; de Groot, Tamara; Tintor, Nico; Rep, Martijn; Takken, Frank L. W.
Abstract: Fusarium oxysporum (Fo) is best known as a host‐specific vascular pathogen causing major crop losses. Most Fo strains, however, are root endophytes potentially conferring endophyte‐mediated resistance (EMR). EMR is a mechanistically poorly understood root‐specific induced resistance response induced by endophytic or nonhost pathogenic Fo strains. Like other types of induced immunity, such as systemic acquired resistance or induced systemic resistance, EMR has been proposed to rely on the activation of the pattern‐triggered immunity (PTI) system of the plant. PTI is activated upon recognition of conserved microbe‐associated molecular patterns (MAMPs) of invading microbes. Here, we investigated the role of PTI in controlling host colonization by Fo endophytes and their ability to induce EMR to the tomato pathogen Fo f. sp. lycopersici (Fol). Transgenic tomato and Arabidopsis plants expressing the Fo effector gene Avr2 are hypersusceptible to bacterial and fungal infection. Here we show that these plants are PTI‐compromised and are nonresponsive to bacterial‐ (flg22) and fungal‐ (chitosan) MAMPs. We challenged the PTI‐compromised tomato mutants with the EMR‐conferring Fo endophyte Fo47, the nonhost pathogen Fom (a melon pathogen), and with Fol. Compared to wild‐type plants, Avr2 ‐tomato plants became hypercolonized by Fo47 and Fom. Surprisingly, however, EMR towards Fol, induced by either Fo47 or Fom, was unaffected in these plants. These data show that EMR‐based disease resistance is independent from the conventional defence pathways triggered by PTI, but that PTI is involved in restricting host colonization by nonpathogenic Fo isolates. Abstract : Whereas MAMP‐triggered immunity restricts growth of pathogenic and endophytic Fusarium oxysporum, it does not restrict the endophyte‐mediated resistance conferred by the latter.